COMPREHENSIVE REVIEW OF SEX DIFFERENCES IN CARDIOVASCULAR PHARMACOLOGY - Ali Mana Hutailan Almuhmidhi, ‏Hussain Mahdi Hassan ALYAMI ‏, Salem Saleh Hamad Al Falakah, Sheikha Saleh Hassan, Mohammd Ahmad Ali Alzogly, Saad Saud Hamad Alyami, Sultan Nasser Mahdi Almuhri, Hussein Mohammed FahidAlsogor, (Chelonian Research Foundation, 2022)
Cardiovascular pharmacologics, sex differences, and the following topics—pharmacokinetics, pharmacodynamics, and clinical outcome—play significant roles in this review. It deals with the importance of considering sex-related differences in cardiovascular drugs and thus highlights the notion of customized therapeutic strategies to improve treatment outcomes holistically. A review was conducted, and central findings from recent studies emphasizing sex hormones, genetic factors, and physiological status's role in drug responses were discussed. Moreover, it illuminates the effects of sex gaps in activity, security, and the unfavourable results of medications. This review provides excellent insight into sex-based variations in cardiovascular pharmacology, which advance the scientific knowledge of sex-specific medicine and thus aid in personalized medicine development. Keywords: sex differences, cardiovascular pharmacology, pharmacokinetics, pharmacodynamics, and personalized medicine.